The expansion of later Acheulean hominins into the Arabian Peninsula. Issue 1 (December 2018) - Scerri, Eleanor; Shipton, Ceri; Clark-Balzan, Laine; Frouin, Marine; Schwenninger, Jean-Luc; Groucutt, Huw; Breeze, Paul; Parton, Ash; Blinkhorn, James; Drake, Nick; Jennings, Richard; Cuthbertson, Patrick; et al.
Abstract The Acheulean is the longest lasting cultural–technological tradition in human evolutionary history. However, considerable gaps remain in understanding the chronology and geographical distribution of Acheulean hominins. We present the first chronometrically dated Acheulean site from the Arabian Peninsula, a vast and poorly known region that forms more than half of Southwest Asia. Results show that Acheulean hominin occupation expanded along hydrological networks into the heart of Arabia from Marine Isotope Stage (MIS) 7 until at least ~190 ka ̶ the youngest documented Acheulean in Southwest Asia. The site of Saffaqah features Acheulean technology, characterized by large flakes, handaxes and cleavers, similar to Acheulean assemblages in Africa. These findings reveal a climatically-mediated later Acheulean expansion into a poorly known region, amplifying the documented diversity of Middle Pleistocene hominin behaviour across the Old World and elaborating the terminal archaic landscape encountered by our species as they dispersed out of Africa.